Long-Term Results of Femtosecond Laser–Enabled Keratoplasty With Zig-Zag Trephination. Issue 1 (January 2019) - Wade, Matthew; Muniz Castro, Hannah; Garg, Sumit; Kedhar, Sanjay; Aggarwal, Sahil; Shumway, Caleb; Farid, Marjan
Abstract : Purpose: To report long-term visual and astigmatism outcomes in cases of zig-zag femtosecond laser–enabled penetrating keratoplasty (FLEK). Methods: Retrospective review. Three hundred thirty-five eyes of 287 patients underwent (FLEK) with a zig-zag incision pattern. Patients were assessed preoperatively and underwent postoperative comprehensive examinations at standard intervals of 1, 3, 6, 9, and 12 months, and 6 months thereafter. Postoperative uncorrected distance visual acuity and spectacle-corrected distance visual acuity and manifest and topographical (Mrx cyl and Topo cyl) astigmatism were compared with preoperative values. Results: Three hundred thirty-five eyes received FLEK with zig-zag configuration. Data are presented for the last recorded visit before any refractive procedure. Sutures were removed in 202 of 335 eyes at an average time to removal of 1.3 ± 1.1 years, and a mean follow-up period of 2.9 ± 2.1 years (range 0–10 years). After full suture removal, mean uncorrected distance visual acuity and spectacle-corrected distance visual acuity were logarithm of the minimum angle of resolution 0.84 (Snellen 20/138) ± 0.55 and 0.33 (Snellen 20/42) ± 0.33, respectively. Mean Mrx cyl and Topo cyl of these groups were 3.38 ± 2.22 and 4.77 ± 3.15, respectively. Of the total number of grafts, the rate of graft rejections was 14.0%, and the failure rate was 5.6%. Conclusions: The femtosecond laser–generated zig-zag–shaped incision results in lower manifest and topographical astigmatism than the reported average for conventional penetrating keratoplasty. Graft rejection and failure rates are similar to published data for conventional penetrating keratoplasty.